Efek Refugia terhadap Keberadaan Musuh Alami di Sawah di Desa Kuluran, Kalitengah, Lamongan - Noni Rahmadhini; Didik Utomo Pribadi; Arika Purnawati (UPN VETERAN JAWA TIMUR, 2018)
Refugia is a microhabitat for natural enemies (predators and parasitoid) to breed that is planted around cultivated plants. The purpose of this study was to determine the effect of the existence of refugia on the abundance of natural enemies in the fields. The method used is the survey method. Observation of natural enemy populations is carried out visually and directly observed. The trap tool used is pitfall and sweep net. The results of the observation showed that 2 families of insects were Branconidae which acted as parasitoid and Collembola which acted as decomposers.